Composição química e atividade antioxidante de diferentes espécies de pitaias - Esgote Junior, João Diniz (2017)
Oxidative stress is a phenomenon that occurs due to deficiencies in the body to combat the emergence and proliferation of reactive oxygen species. The balance between a formation and the prevention against the species can happen by the action of the own organism, or ingestion of nutrients with antioxidant activities, being these systems of action as active agents of prevention for the human being. As the main sources of antioxidants available to man and fruits and vegetables, foods are in the diet and widely studied by science. An example of fruit that has antioxidant activity is Pitaya. Pitaya is a fruit of the Cactaceae family, with the main species Hylocereus Undatus (Hu) and Hylocereus Costaricensis (Hc), and in the last years they have been studied for their noble composition in antioxidants. Pitaya, when evaluated against various antioxidant quantification techniques, showed relevant and promising results, such as total phenolic results equal to 33.67 ± 1.59 mg GAE / 100 g of fresh sample in the peel of the Hu species 52.36 ± 5.30 mg GAE / 100 g fresh sample in the pulp of the Hu species whereas for the Hc peel the value found was 44.80 ± 3.96 mg GAE / 100 g fresh sample, and the pulp provided a value of 66.73 ± 5.26 mg GAE / 100 g fresh sample. These values can be compared to other fruits already present in the diet of the human being, such as the banana, which in its pulp the amount of total phenolics reaches 57,13 ± 3,64 mg GAE/ 100 g of fresh sample, or the passion fruit that has 37.91 ± 0.14 mg GAE / 100 g fresh sample. Another difference of pitaya is the amount of vitamin C that has been found in its composition, reaching values equal to 29.93 ± 0.77 mg / 100 g fresh sample in the Hc pulp and 28.40 ± 3.44 mg / 100 g of fresh sample in the Hu pulp, such values are higher than those of pear, peach, banana, avocado and apple, where all have amounts less than 20.0 mg / 100 g of vitamin C fresh sample in their composition. In this sense, pitaya is able to replace several fruits already present in the diet, being able to be source of nutrients and have the ability to use the fruit in its entirety, including its peel.